Microrganismos de solos amazônicos com potencial na bioconversão de material ligninocelulósico em sólidos solúveis - Braga, Carla Maria de Souza (2009)
The cane bagasse, as other vegetable residues, as the sawdust of woody species, are not very used and they can generate biotechnical products of economic interest, in case they are better used. Amazonia is an area where the vegetable refuse is high and very a little used, being a lot of times, throwed away in the environment. Considering the use of organic matter of vegetable origin and present microorganisms in the soil with potential to metabolize cellulose, hemicellulose and lignin, the present research sought to select microorganisms of the soil able to convert vegetable material in soluble solids, as a pré-product for the production of biotechnical products, as alcohol, sugar among others. For that, laboratory experiments were accomplished using regional soils and, bacteria and fungi isolated of those soils to evaluate its potentials in converting cane bagasse (Saccharum sp L.) and assacu sawdust (Hura crepitans L.) in soluble solids. It was also tested, the effect of the addition of high doses of nitrogen in the medium and of high temperature in the accumulation of those solids. The results indicated that there were differences among the microbiotas of the soils to produce soluble solids using those two vegetables materials as carbon sources. The microbiotas of the urucu soils provided higher accumulations of soluble solids that those of the INPAs soils. There were significant differences among the fungi and among the bacteria isolated of those soils in relation to the accumulation of soluble solids. Increasing the amount of nitrogen in the medium resulted in higher accumulations of soluble solids. There were higher accumulations of soluble solids at the temperature of incubation of 39° C when compared with 26° C. The fungi that provided higher accumulations of soluble solids were those identified as INPA 4FC, INPA 5FA, INPA 7FC and INPA 8FA. The bacteria that provided higher accumulations of soluble solids were the identified as INPA 1BA, INPA 5BA and INPA 6BA.